Self learning kits in communication arts (English) for grade four children at the Tahanan Special School - Del Rosario, Angelina A. (College of Education, University of the Philippines Diliman, 1975)
The purpose of the study is to present sample lessons programmed for individualized instruction in language for children who are pedagogically labelled as socially alienated. The study centers its attention on 8 pupils taking into consideration their social and intellective factors, socio-economic status and parents' educational background. It deals with the learning characteristics, language and academic performance of the subjects. Finally, it proposed a program for each of them which serves as the basis for the use of the Self-Learning Kits.